QUALITY OF LIFE AS A SOCIAL AND ECONOMIC CATEGORY AND AS AN OBJECT OF STATISTICAL RESEARCH - I. Romaniuk (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The gnosiological roots of the concept of quality of life as a social and economic category are analyzed in the article. International approaches to the definition of quality of life are investigated in order to study it as an object of statistical research.